2014
DOI: 10.3390/molecules19068518
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties, Antioxidant Activity and Mineral Contents of Pineapple Genotypes Grown in China

Abstract: Abstract:The fruit physico-chemical properties, antioxidant activity and mineral contents of 26 pineapple [Ananas comosus (L.) Merr.] genotypes grown in China were measured. The results showed great quantitative differences in the composition of these pineapple genotypes. Sucrose was the dominant sugar in all 26 genotypes, while citric acid was the principal organic acid. Potassium, calcium and magnesium were the major mineral constituents. The ascorbic acid (AsA) content ranged from 5.08 to 33.57 mg/100 g fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
59
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 29 publications
14
59
2
2
Order By: Relevance
“…It was different with the present study which demonstrated that ethanolic peel extract of Bogor pineapple showed IC 50 DPPH 0.13 µg/ml classified as a very strong antioxidant. The previous research presented that methanol fruit pulp extract of MD2 genotype pineapple gave the highest DPPH scavenging activities (22.85 µmol TE/fresh weight) among 26 six genotypes of pineapples from China [11]. A study by Kongsuwan et al [20] exhibited that frozen fruit pulp Nanglae pineapple showed higher DPPH scavenging activity (152.93 mol TE/100 g fresh weight) than Phulae pineapple (118 mol TE/100 g fresh weight).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was different with the present study which demonstrated that ethanolic peel extract of Bogor pineapple showed IC 50 DPPH 0.13 µg/ml classified as a very strong antioxidant. The previous research presented that methanol fruit pulp extract of MD2 genotype pineapple gave the highest DPPH scavenging activities (22.85 µmol TE/fresh weight) among 26 six genotypes of pineapples from China [11]. A study by Kongsuwan et al [20] exhibited that frozen fruit pulp Nanglae pineapple showed higher DPPH scavenging activity (152.93 mol TE/100 g fresh weight) than Phulae pineapple (118 mol TE/100 g fresh weight).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Kongsuwan et al [20] presented that TPC and vitamin C of frozen fruit pulp of Phulae pineapple (26.20 mg GAE/100 g and 18.88 mg/100 g fresh weight, respectively) were higher than Nanglae pineapple (20.28 mg GAE/100 g and 6.45 mg/100 g fresh weight). The previous study [11] expressed that TPC in methanolic fruit pulp extract of MD2 pineapple genotype (77.55 mg GAE/100 g fresh weight) was the highest TPC among 26 six pineapple genotypes. The methanolic peel extract of pineapple from Egypt exhibited that FPW showed higher TPC than UFPW [22].…”
Section: Tpcmentioning
confidence: 99%
See 3 more Smart Citations